Political Parties and Euroscepticism - Topaloff, L.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2012)
An exploration of what drives party-based Euroscepticism and why some parties are Eurosceptic. This book looks at what makes mainstream opposition parties careful not to appear Eurosceptic and asks whether Euroscepticism is an aberration of politics, an extreme populist ideology, or just politics as usual.
Keywords: European Union; Comparative politics; Europe—Politics and government; Political science; United States—Politics and government; International relations; European Union Politics; Comparative Politics; European Politics; Political Science; US Politics; International Relations